The Implementation of Embodied Learning: A Literature Review - Sani, Yulvia; Wardany, Ossy Firstanti; Herlina, Heni; Vernanda, Genesa (Edukasi, 2021)
This literature review aims to determine the implementation of the embodied learning approach in children. The research method used is a narrative review of ten articles that have met the criteria. The criteria for the article are to be found in Google Scholar, published in the last 8 years (2012-2021), and the title contains "Embodied Learning". There are five things that are studied, namely the concept of embodied learning; the relationship between psychology, education, and the environment; student age; tools and materials (technology); and materials that can be provided through an embodied learning approach. This literature review shows that embodied learning is a learning approach that emphasizes the involvement of the body in the process of receiving and responding to the material. Embodied learning can be implemented to improve children's language skills, motor skills, memory skills, and learning foreign language material. The ages of students who accept this embodied learning approach are range from 4 years to 12 years, or kindergarten and elementary school ages. From the ten articles studied, it was found that the involvement of the body in the learning process can build information in students' long-term memory.